Age-dependent loss of induced regulatory T cell function exacerbates liver ischemia-reperfusion injury. (November 2018) - Liu, Rui; Zhang, Shaopeng; Ma, Wenxuan; Lu, Hao; Gao, Ji; Gan, Xiaojie; Ju, Zheng; Gu, Jian; Lu, Ling
Highlights: This work represents our original findings demonstrating that iTregs isolated from Young-mice exhibited stronger immunosuppressive ability in vitro and had a greater response during IRI in vivo . Our results showed that Young-mice were less susceptible to IRI as a result of having iTregs with stronger immune suppressive ability in vitro and in vivo . Adoptive transfer of iTregs ameliorated liver IRI and promoted liver recovery with decreased levels of interferon-γ (IFN-γ) and interleukin-17 (IL-17). Our findings suggest that the exacerbated IRI observed in aged-mice is a result of decreased iTreg function while Young-mice have an increased tolerance to IRI resulting from iTreg protection in the liver following injury. Improving iTreg function is important for disease treatment in elder patients.This mechanism of how age affects function and induction of iTregs may be beneficial in utilizing iTreg-related immune therapy. Abstract: Previous studies demonstrate that the number of induced regulatory T cells (iTregs) increases in aged mice. However, these studies do not characterize iTregs across different ages or how these immune modulators contribute to the dysregulation of immunity in murine disease models. Therefore, this study aimed to examine the relationship between age and iTreg function using a mouse model of hepatic ischemia-reperfusion injury (IRI). In this model, aged-mice suffered more serious injury than Young-mice, with higher serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and higher histological scores from liver biopsies. iTregs isolated from Young-mice exhibited stronger immunosuppressive ability in vitro and had a greater response during IRI in vivo . In addition, aged-mice that were pretreated with iTregs generated in Young-mice (Y-iTregs) had alleviated injury compared with mice pretreated with iTregs from aged-mice (A-iTregs) or no treatment group. Adoptive transfer of iTregs ameliorated liver IRI and promoted liver recovery with decreased levels of interferon-γ (IFN-γ) and interleukin-17 (IL-17). These results demonstrate that the exacerbated IRI observed in aged-mice is a result of decreased iTreg function. Therefore, improving iTreg function is important for disease treatment in elder patients.